Thymic B Cell-Mediated Attack of Thymic Stroma Precedes Type 1 Diabetes Development - Pinto, Ana Isabel; Smith, Jennifer; Kissack, Miriam R.; Hogg, Karen G.; Green, E. Allison (Frontiers in Immunology, 2018)
Type 1 diabetes results from a co-ordinated autoimmune attack of insulin producing beta cells in the pancreas by the innate and adaptive immune systems, beta cell death being predominantly T cell-mediated. In addition to T cells, peripheral B cells are important in type 1 diabetes progression. The thymus of mice and man also contain B cells, and lately they have been linked to central tolerance of T cells. The role of thymic B cells in type 1 diabetes is undefined. Here we show there are abnormalities in the thymic B cell compartment prior to beta cell destruction and type 1 diabetes manifestation. Using non-obese diabetic (NOD) mice, we document that preceding type 1 diabetes development, there is significant accumulation of thymic B cells-partly through in situ development- and the putative formation of ectopic germinal centres. In addition, in NOD mice we quantify thymic plasma cells and observe in situ binding of immunoglobulins to undefined antigens on a significant proportion of medullary thymic epithelial cells. In contrast, no ectopic germinal centres, or pronounced intrathymic autoantibodies are detectable in animals not genetically predisposed to developing type 1 diabetes. Binding of autoantibodies to thymic stroma correlates with apoptosis of medullary thymic epithelial cells, including insulin-expressing cells. In contrast, apoptosis of medullary thymic epithelial cells was decreased by 50% in B cell deficient NOD mice suggesting intrathymic autoantibodies may selectively target certain medullary thymic epithelial cells for destruction. Futhermore, we observe that these thymic B cell-associated events correlated with an increased prevalence of premature thymic emigration of T cells. Together our data suggests that the thymus may be a principal autoimmune target in type 1 diabetes and contributes to disease progression.